2005
DOI: 10.1111/j.0022-202x.2005.23699.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Cornified Envelope Family in Differentiating Epithelia—Response to Calcium and Ultraviolet Irradiation

Abstract: The late cornified envelope (LCE) gene cluster within the epidermal differentiation complex on human chromosome one (mouse chromosome three) contains multiple conserved genes encoding stratum-corneum proteins. Within the LCE cluster, genes form "groups" based on chromosomal position and protein homology. We link a recently accepted nomenclature for the LCE cluster (formerly XP5, small proline-rich-like, late-envelope protein genes) to gene structure, groupings, and chromosomal organization, and carry out a pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
180
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(188 citation statements)
references
References 38 publications
6
180
0
Order By: Relevance
“…Expression of the Sprr and Lce genes is associated with epidermal terminal differentiation [38] and psoriasis [39]. Lce genes are organized in three sub-clusters which exhibit common regulation of gene expression [40]. In the mouse, genes from all groups are also expressed in stomach, umbilical cord and cornea (http://biogps.gnf.org/?referer¼symatlas#goto¼ welcome).…”
Section: Differential Regulation Of Genes and Gene Families Between Tmentioning
confidence: 99%
“…Expression of the Sprr and Lce genes is associated with epidermal terminal differentiation [38] and psoriasis [39]. Lce genes are organized in three sub-clusters which exhibit common regulation of gene expression [40]. In the mouse, genes from all groups are also expressed in stomach, umbilical cord and cornea (http://biogps.gnf.org/?referer¼symatlas#goto¼ welcome).…”
Section: Differential Regulation Of Genes and Gene Families Between Tmentioning
confidence: 99%
“…8 This region is enriched for genes expressed during epidermal differentiation including loricrin, involucrin, filaggrin, the small proline-rich protein genes, and the LCE genes. 9,10 With 18 members, the LCE gene family is divided into six groups, LCE1 to LCE6, based on similarities of amino acid sequences, genomic organization, and patterns of expression. 9 The role of the LCE proteins in epidermal biology has not been extensively studied.…”
mentioning
confidence: 99%
“…9,10 With 18 members, the LCE gene family is divided into six groups, LCE1 to LCE6, based on similarities of amino acid sequences, genomic organization, and patterns of expression. 9 The role of the LCE proteins in epidermal biology has not been extensively studied. In mice, it was observed that members of the Lce1 group are expressed rather late in epithelial development, where they are incorporated into the cornified envelope via cross-linking by transglutaminases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genes encoding S100A8 and A9 are localized to the epidermal differentiation complex (EDC) on human chromosome 1q21.3, together with at least 58 genes involved in keratinocyte terminal differentiation. 12 Along with several other EDC genes, S100A8 and S100A9 are strongly overexpressed in psoriasis. 13 While both linkage and association to the EDC have been reported in psoriasis, 14 these results remain to be widely confirmed.…”
mentioning
confidence: 99%